Roosters As a Source of Ideas for Creating Graphic Art Work with Silkscreen Technique - Ismi Aryati (Gelar : Jurnal Seni Budaya, 2019)
This final task is a visualization based on the imagination in the form of silkscreen work with Rooster. The problem discussed in this final task is what is the uniqueness of rooster that becomes our correlation in life, the reason why choosing a life of rooster as a source of ideas in creating silkscreen work and how Visualize the rooster theme in silkscreen work. The purpose of writing this final task is to explain how the habits and characteristics owned by the Rooster can give a learning in our lives. Which gives reasons on the selection of Rooster that was appointed as the source of ideas in the creation of silkscreen works, visualizing the theme of rooster in silkscreen work. The rooster has unique habits and characteristics. An example of a rooster's habit is crowed in the morning and how it survives. In the characteristics of rooster that is rarely known by Banayak people is, when the head of the rooster can be in the same position when we shake the Badannnya. The balance in the rooster becomes its own characteristic. With the life of the rooster that gives an idea of the author's life that will be visualized into graphic artwork. The life of Rooster that gives its own background to the author of the Life of the rooster theme is interesting so it is lifted in the background of this final task introduction. The creation of this work is expected to attract the attention of the connoisseur of the art of life in the rooster that visualized in silkscreen work to pour the idea, the visualization of the life of Rooster is also supported by the media canvas with a Silkscreen technique. The work depicts the life of the rooster and how the results of the observations and expressions that the author poured into the work.Keywords: rooster, graphic arts, silkscreen